Halogen-free flame-retardant polyethylene core layer material for decoration fireproof aluminum-plastic panel

The halogen-free flame-retardant polyethylene core layer material for decoration and decoration of fire-resistant aluminum-plastic panels is prepared through specific formulas and processes, which solves the problem that existing materials are difficult to take into account both flame retardant effects and mechanical properties, and achieves the effect of excellent flame retardant performance and good mechanical properties of the materials.

CN119570142AInactive Publication Date: 2025-03-07SHANDONG BOXIONG CONSTR ENG CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510134527.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing halogen-free flame-retardant polyethylene core layer materials for fire-resistant aluminum-plastic panels are difficult to take into account both the flame retardant effect and the mechanical properties, resulting in excellent flame retardant performance but the mechanical properties are degraded, or the mechanical properties are good but the flame retardant performance is not ideal.

Method used

The halogen-free flame-retardant polyethylene core layer materials for decoration and decoration of fire-resistant aluminum-plastic panels are prepared using specific formulas and processes, including low-density polyethylene, high-density polyethylene, ethylene-ethyl acrylate copolymer, modified sepiolite-loaded phytic acid, ethylene octene copolymer coated expanded graphite, modified hydroxide flame retardant and modified nanohydrotalcite flame retardant. Through the preparation process of modified sepiolite and nanohydrotalcite, the flame retardant and mechanical properties of the materials are improved.

Benefits of technology

The halogen-free flame-retardant polyethylene core layer material has achieved good mechanical properties and excellent flame-retardant properties, and the tensile strength, elongation of break, impact strength, bending strength and oxygen index all meet higher standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a halogen-free flame-retardant polyethylene core layer material for a decoration fireproof aluminum-plastic panel, and belongs to the technical field of building fireproof materials. The halogen-free flame-retardant polyethylene core layer material for the decoration fireproof aluminum-plastic panel is prepared from low-density polyethylene, high-density polyethylene, an ethylene-ethyl acrylate copolymer, modified sepiolite-loaded phytic acid, ethylene-octene copolymer coated expanded graphite, a modified hydroxide flame retardant, a modified nano hydrotalcite flame retardant and a lubricant polyethylene wax. According to the halogen-free flame-retardant polyethylene core layer material for the decoration fireproof aluminum-plastic panel, the tensile strength is 24.5 to 25.2 MPa, the elongation at break is 41.6 to 47.5 percent, the impact strength is 47.1 to 48.5 kJ / m < 2 >, the bending strength is 25.9 to 27.2 MPa, and the oxygen index is 40.4 to 41.1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels, belonging to the technical field of building fireproof materials. Background Art

[0002] The fireproof aluminum-plastic panel for decoration, also known as the fireproof aluminum-plastic composite panel, is mainly composed of three layers of panels, which are the inorganic flame-retardant plastic core panel (also called the core layer) in the middle, the aluminum metal panel on the front and the aluminum metal bottom panel on the back. The inorganic flame-retardant plastic core panel is obtained by passing the corresponding granules through a sheet extrusion molding machine. The material used to make the core panel (core layer) is flame-retardant modified polyethylene granules (referred to as flame-retardant polyethylene). This flame-retardant polyethylene is obtained by adding corresponding flame retardants to polyethylene for melt mixing. The added flame retardants can be classified into three major flame retardant systems based on their composition. One is the bromine-antimony composite flame retardant system, which is mainly composed of bromine-containing organic flame retardants and Sb 2 O 3 The first is a halogen system; the second is a nitrogen-phosphorus composite flame retardant system; the third is a metal oxide flame retardant system. The second and third flame retardant systems are halogen-free systems. For flame-retardant polyethylene using a bromine-antimony composite flame retardant system, the amount of flame retardant used is small and the flame retardant effect of the sheet made from it is good, but a large amount of harmful HBr and SbBr is released when the plastic burns. 3 Gas and black smoke, with molten droplets, are highly polluted to the environment, and can easily cause suffocation and death in severe cases. For flame-retardant polyethylene using a nitrogen-phosphorus flame-retardant composite system, the resulting board has better flame retardancy, less smoke and no molten droplets when burned, but the flame retardant of this flame-retardant polyethylene has poor compatibility with polyethylene, and some flame retardants may even precipitate during processing, affecting the appearance and surface adhesion of the plastic core board. For flame-retardant polyethylene using a metal oxide flame retardant system, the flame retardancy of the sheet material manufactured therefrom is good, there is no droplet phenomenon, the flame retardant has a smoke suppression function, and the flame retardant itself does not produce harmful gases when burning. However, this flame retardant relies on the water it produces to achieve the purpose of flame-retardant polymer materials. Therefore, the flame retardant needs to be added in a higher amount, generally 50~60% (weight percentage) or more, to play the role of flame-retardant polymers. However, a high addition amount can easily cause a significant decrease in mechanical properties such as toughness and strength of polymer materials. Therefore, the halogen-free flame retardant system of the flame-retardant polyethylene core material for fire-resistant aluminum-plastic panels is still difficult to achieve excellent flame retardant properties without significantly affecting mechanical properties.

[0003] Chinese patent CN116478463A discloses a fireproof aluminum-plastic plate core material and its preparation process. The formula of the fireproof aluminum-plastic plate core material is: 15-30 parts of low-density polyethylene, 5-15 parts of ethylene-octene copolymer, 30-50 parts of aluminum hydroxide, 10-15 parts of anhydrous magnesium carbonate, 5-10 parts of calcium stearate, 5-8 parts of silicon dioxide, 8-15 parts of coupling agent, 5-10 parts of smoke suppressant, 1-3 parts of reinforcing and toughening agent, 0.1-0.5 parts of titanium dioxide, 0.2-0.5 parts of halogen-free composite flame retardant, 0.1-0.5 parts of surface treatment agent, 0.1-0.5 parts of PE and 5-10 parts of modified resin. Although the fireproof aluminum-plastic plate core material obtained in this patent has a relatively high oxygen index, all above 34, the tensile strength is relatively low, and the maximum can only reach 8.6MPa.

[0004] Chinese patent CN109111617A discloses a flame retardant core layer of aluminum-plastic plate and aluminum-plastic plate, the technical scheme of which is based on weight parts, including 30-50 parts of base resin, 30-40 parts of flame retardant, 0.5-1.5 parts of flame retardant synergist, 1-2 parts of anionic surfactant, 2-4 parts of compatibilizer, 1-2 parts of antioxidant and 0.5-1.5 parts of antibacterial agent; the base resin includes low-density polyethylene, polypropylene, ethylene-octene copolymer and ethylene-ethyl acrylate, and the weight ratio of low-density polyethylene, polypropylene, ethylene-octene copolymer and ethylene-ethyl acrylate copolymer is 6:2:1:1; the flame retardant includes magnesium hydroxide and expandable graphite, and the weight ratio of magnesium hydroxide to expandable graphite is 6:1. The flame retardant core layer of aluminum-plastic plate obtained by this patent has good mechanical properties, but the flame retardant performance is not ideal, and the oxygen index is only up to 34.1.

[0005] From the above, it can be seen that the current halogen-free flame-retardant polyethylene core layer material for fireproof aluminum-plastic panels is still difficult to take into account both flame retardant effect and mechanical properties. Therefore, the development of halogen-free flame-retardant polyethylene core layer materials with good mechanical properties and excellent flame retardant properties has very important practical value and realistic significance for the decoration of fireproof aluminum-plastic panels. Summary of the invention

[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a halogen-free flame-retardant polyethylene core layer material for decorative fireproof aluminum-plastic panels, to achieve the following invention objectives: to prepare a halogen-free flame-retardant polyethylene core layer material for decorative fireproof aluminum-plastic panels with good mechanical properties and excellent flame retardant properties.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels, wherein the specific formula of the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels is, in parts by weight: 160~250 parts of low-density polyethylene, 80~140 parts of high-density polyethylene, 15-70 parts of ethylene-ethyl acrylate copolymer, Modified sepiolite loaded with phytic acid 10-35 parts, 5-25 parts of ethylene octene copolymer coated expanded graphite, 15-55 parts of modified hydroxide flame retardant, 5-20 parts of modified nano hydrotalcite flame retardant, Lubricant polyethylene wax 4-12 parts; The low-density polyethylene has a melting temperature of 105-115°C and a density of 0.916-0.925 g / cm 3 , melt flow rate is 10~25g / 10min at 190℃ / 2.16kg; The high-density polyethylene has a melting temperature of 115-130°C and a density of 0.944-0.954 g / cm 3 , the melt flow rate is 8~13g / 10min at 190℃ / 2.16kg; The ethylene-ethyl acrylate copolymer has a melting temperature of 95-105°C and a density of 0.920-0.935 g / cm 3 , the melt flow rate is 5~11g / 10min at 190℃ / 2.16kg, and the content of ethyl acrylate is 15~20wt%; The following are further improvements to the above technical solution: Step 1: Preparation of modified sepiolite loaded with phytic acid After the nano-sepiolite is placed in a 90-120° C. oven and dried for 7-14 hours, the nano-sepiolite is added to a dispersion reactor, and then acetone and tetradecyl dimethyl tertiary amine are added. The stirring rate is controlled at 5500-9000 rpm, and the dispersion is vigorously stirred for 6-14 hours. The stirring rate is reduced to 2500-4800 rpm, and then the temperature is raised and kept constant at 40-60° C., and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is added under a condensation reflux state. After the constant temperature dispersion reaction is performed for 4-9 hours, the temperature is lowered to room temperature, and then phytic acid is added. After the phytic acid is completely dissolved, the dispersion is stopped, and the material is allowed to stand for 24-45 hours. The material is filtered, and the filtered solid is placed in a 40-70° C. oven and dried for 5-10 hours to obtain to the phytic acid-loaded sepiolite, then add the maleic anhydride grafted polyethylene and toluene into a dry and clean stirred reactor, control the stirring rate at 2000-4000 rpm, raise the temperature and keep the temperature constant at 110-130° C., stir at the constant temperature under condensation reflux until the maleic anhydride grafted polyethylene is completely dissolved, then add the phytic acid-loaded sepiolite, continue to stir at the constant temperature for 7-15 hours after the addition is completed, and then drop anhydrous ethanol into the reactor at a rate of 0.5-1.3 mL / s. After the dropwise addition is completed, continue to stir for 1-2.5 hours, cool to room temperature, filter the discharged material, wash the filtered solid with anhydrous ethanol for 2-4 times, and dry it at 70-90° C. for 5-8.5 hours to obtain the modified sepiolite loaded with phytic acid; The particle size of the nano sepiolite is 20-200 nm; The density of the maleic anhydride grafted polyethylene is 0.93-0.97 g / cm 3 , the melt index is 3~8g / 10min at 190℃ / 2.16kg, and the melting temperature is 120~130℃; The mass ratio of the nano-sepiolite, acetone, tetradecyl dimethyl tertiary amine, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane and phytic acid is 35-60:150-330:1-5:6-25:25-55; The mass ratio of the phytic acid-loaded sepiolite, maleic anhydride grafted polyethylene, toluene and anhydrous ethanol is 30-80:8-20:190-250:80-160.

[0008] Step 2: Preparation of ethylene-octene copolymer-coated expanded graphite Adding ethylene octene copolymer and xylene into a reactor, controlling the stirring rate at 3000-6000 rpm, raising the temperature and keeping the temperature constant at 120-150° C., stirring at the constant temperature under condensation reflux until the ethylene octene copolymer is completely dissolved, then adding expanded graphite, and after the addition is completed, continuing to stir at the constant temperature for 10-17 hours, adding anhydrous ethanol dropwise into the reactor at a rate of 1-2.5 mL / s, and after the addition is completed, continuing to stir for 2-4.5 hours, cooling to room temperature, discharging and filtering, washing the filtered solid with anhydrous ethanol for 2-4 times, and drying at 40-60° C. for 6-10 hours to obtain ethylene octene copolymer-coated expanded graphite; The density of the ethylene octene copolymer is 0.85-0.88 g / cm 3 , the melt index at 190℃ / 2.16kg is 1~3.5g / 10min, the Mooney viscosity at 121℃ / ML1+4 is 18~23MU, and the melting temperature is 48~53℃; The particle size of the expanded graphite is 300-600 mesh; The mass ratio of the ethylene octene copolymer, xylene, expanded graphite and anhydrous ethanol is 10-30:130-290:10-50:80-190.

[0009] Step 3: Preparation of modified hydroxide flame retardant The hydroxide is placed in a 90-110° C. oven and dried for 6-16 hours, then added to a dispersion reactor, and then toluene and sorbitan fatty acid ester are added, and the stirring rate is controlled to be 5000-9500 rpm, and the stirring rate is reduced to 2000-4500 rpm. Then, the temperature is raised and kept constant at 70-90° C., 3-isocyanate propyltrimethoxysilane is added under a condensation reflux state, and the dispersion reaction is carried out at a constant temperature for 3-6 hours, and then liquid polybutadiene rubber is added, and the dispersion reaction is continued for 5-9 hours, and then the temperature is cooled to room temperature, and the material is filtered, and the filtered solid is washed with anhydrous ethanol for 2-4 times, and then dried in an oven at 60-90° C. for 4-9 hours to obtain a modified hydroxide flame retardant; The hydroxide is one of powdered aluminum hydroxide and powdered magnesium hydroxide, and the particle size is 0.5-3 μm; The liquid polybutadiene rubber has a number average molecular weight of 2000-5500 g / mol and a viscosity of 3-8 Pa·s at 40° C.; The liquid polybutadiene rubber is one of carboxyl-terminated liquid polybutadiene rubber and hydroxyl-terminated liquid polybutadiene rubber; The mass ratio of the hydroxide, toluene, sorbitan fatty acid ester, 3-isocyanate propyltrimethoxysilane and liquid polybutadiene rubber is 60-110:160-360:1-4:10-35:10-40.

[0010] Step 4: Preparation of modified nano-hydrotalcite flame retardant After the nano-hydrotalcite is placed in an oven at 80-100° C. and dried for 7-15 hours, the nano-hydrotalcite is added to a dispersion reactor, and then xylene and octylphenol polyoxyethylene ether are added, and the stirring rate is controlled to be 8000-10000 rpm, and the dispersion is vigorously stirred for 6-10 hours, and the stirring rate is reduced to 3000-4500 rpm, and then the temperature is raised and kept constant at 100-140° C., and aromatic diacyl chloride is added under a condensation reflux state, and the dispersion reaction is continued at a constant temperature for 5-11 hours, and then a long-chain hydrocarbon primary amine is added, and the dispersion reaction is continued for 6-10 hours, and then the temperature is cooled to room temperature, and the material is filtered, and the filtered solid is washed with anhydrous ethanol for 2-4 times, and then dried in an oven at 60-80° C. for 8-13 hours to obtain a modified hydroxide flame retardant; The particle size of the nano hydrotalcite is 10-100 nm; The aromatic diacyl chloride is one of 1,4-phenylenediacetyl chloride, 2,2-bipyridine-5,5-acyl chloride, and 4,4'-diacyl chloride diphenyl ether; The long-chain hydrocarbon primary amine is one of 12-tricosylamine, octadecyl primary amine, and coconut oil alkyl primary amine; The mass ratio of the nano-hydrotalcite, xylene, octylphenol polyoxyethylene ether, aryl diacyl chloride and long-chain hydrocarbon primary amine is 20-70:140-300:1-2.5:7-19:9-25.

[0011] Step 5: Preparation of halogen-free flame-retardant polyethylene core material According to the specific formula of the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels in parts by weight, corresponding parts by weight of low-density polyethylene, high-density polyethylene, ethylene-ethyl acrylate copolymer, modified sepiolite loaded with phytic acid, ethylene-octene copolymer coated expanded graphite, modified hydroxide flame retardant, modified nano-hydrotalcite flame retardant and lubricant polyethylene wax are put into a high-speed mixer and stirred and mixed. The mixing temperature is controlled at 60-95° C. and the stirring speed is 600-950 rpm. After stirring and mixing for 15-35 minutes, the mixed materials are sent to a twin-screw extruder. The heating zone of the twin-screw extruder is controlled at 170-220° C. and the die head temperature is controlled at 190-210° C. The extrusion granulation is carried out, and the obtained resin particles are air-cooled to room temperature to obtain the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels.

[0012] Compared with the prior art, the present invention achieves the following beneficial effects: 1. The present invention firstly disperses nano-sepiolite in an acetone solvent at a nanometer scale under the dispersing effect of tetradecyl dimethyl tertiary amine, and then uses N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane to modify the internal microporous surface of the nano-sepiolite. After the modification, the internal microporous surface of the sepiolite is covered with primary amine groups and secondary amine groups. Under the strong adsorption effect of the sepiolite, these two functional groups then react with phytic acid, and a large amount of phytic acid is adsorbed and loaded inside the sepiolite. Then, maleic anhydride grafted polyethylene is used to coat the sepiolite loaded with phytic acid. After these process steps, the sepiolite is loaded with a large amount of phytic acid with a very high phosphorus content, and after being coated with maleic anhydride grafted polyethylene, the sepiolite is very compatible with the polyethylene matrix resin and can be evenly dispersed in the polyethylene resin matrix, so that the flame retardant properties of the sepiolite loaded with phytic acid with a high phosphorus content can be fully utilized. At the same time, due to the uniform dispersion of the sepiolite, the mechanical properties of the polyethylene resin matrix will not be affected. Therefore, the modified sepiolite loaded with phytic acid can greatly improve the flame retardant properties of the halogen-free flame retardant polyethylene core material without affecting its various mechanical properties. 2. The present invention coats expanded graphite with ethylene-octene copolymer, thereby promoting the uniform dispersion of expanded graphite in polyethylene matrix resin. Ethylene-octene copolymer is similar to polyethylene molecular structure and has very good compatibility with polyethylene. Moreover, ethylene-octene copolymer is a thermoplastic elastomer with particularly good toughening effect, which can greatly improve the toughness of polyethylene matrix resin. The flame retardant efficiency of expanded graphite is particularly high, which can greatly increase the residual carbon rate in the combustion process of polyethylene resin and significantly reduce the droplet phenomenon in the combustion process of polyethylene resin. After the expanded graphite is coated with ethylene-octene copolymer, the agglomeration phenomenon of expanded graphite in polyethylene matrix resin can be reduced to the greatest extent, thereby reducing the damage of the incorporation of expanded graphite to the mechanical properties of polyethylene resin, and then the effect of expanded graphite on the improvement of the flame retardant properties of polyethylene resin can be fully exerted. 3. After the surface of aluminum hydroxide or magnesium hydroxide is modified by 3-isocyanate propyltrimethoxysilane, the surface of aluminum hydroxide or magnesium hydroxide is covered by isocyanate groups and trimethoxysilane groups, and then reacted with hydroxyl-terminated liquid polybutadiene rubber or carboxyl-terminated liquid polybutadiene rubber, so that the surface of aluminum hydroxide or magnesium hydroxide is finally wrapped by polybutadiene rubber molecules. Polybutadiene is a rubber polymer with very low polarity and has good compatibility with polyethylene resin. In this way, the surface-modified aluminum hydroxide or magnesium hydroxide can be dispersed more evenly in the polyethylene resin matrix, thereby avoiding the damage to the mechanical properties of the polyethylene resin matrix caused by the addition of inorganic flame retardant powder, and at the same time greatly improving the flame retardant effect of the inorganic flame retardant powder on the polyethylene resin; 4. The present invention first uses aromatic diacyl chloride to react with active hydroxyl groups on the surface of nano hydrotalcite to cover the surface of nano hydrotalcite with acyl chloride functional groups, and then the acyl chloride functional groups react with primary amine functional groups in long-chain alkane primary amines. Finally, the surface of the nano hydrotalcite is coated with long-chain hydrocarbon groups. The polarity of the long-chain hydrocarbon groups is relatively low, and the compatibility with the polyethylene resin matrix is ​​relatively good. In this way, the nano hydrotalcite is relatively easy to be dispersed into the polyethylene resin matrix at a nanoscale, and the polyethylene resin matrix has a role in strengthening and toughening and improving the flame retardant performance. In addition, the aromatic diacyl chloride and long-chain alkane primary amine used in the present invention have good heat resistance. After the nano hydrotalcite is coated with these two substances, it can withstand the high temperature in the process of melt extrusion of polyethylene resin, and thus will not affect the various properties of the polyethylene resin matrix due to thermal decomposition; 5. The halogen-free flame-retardant polyethylene core material for fireproof aluminum-plastic panels prepared by the present invention has a tensile strength of 24.5-25.2 MPa, an elongation at break of 41.6-47.5%, and an impact strength of 47.1-48.5 kJ / m 2 , flexural strength 25.9~27.2MPa, oxygen index 40.4~41.1. DETAILED DESCRIPTION

[0013] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0014] Example 1: A halogen-free flame-retardant polyethylene core material for fireproof aluminum-plastic panels for decoration Step 1: Preparation of modified sepiolite loaded with phytic acid After the nano-sepiolite was placed in a 100° C. oven and dried for 11 hours, it was added to a dispersion reactor, and then acetone and tetradecyl dimethyl tertiary amine were added. The stirring rate was controlled at 8500 rpm, and the dispersion was vigorously stirred for 9 hours. The stirring rate was reduced to 3800 rpm, and then the temperature was raised and kept constant at 55° C., and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added under the condensation reflux state. After the constant temperature dispersion reaction was performed for 6 hours, the temperature was lowered to room temperature, and then phytic acid was added. After the phytic acid was completely dissolved, the dispersion was stopped, and the material was allowed to stand for 36 hours. The solid was filtered, and the filtered solid was placed in a 60° C. oven and dried for 8 hours to obtain The phytic acid-loaded sepiolite, then maleic anhydride grafted polyethylene and toluene are added to a dry and clean stirred reactor, the stirring rate is controlled at 3500 rpm, the temperature is raised and kept constant at 125°C, and the maleic anhydride grafted polyethylene is stirred at a constant temperature under condensation reflux until the maleic anhydride grafted polyethylene is completely dissolved, and then the phytic acid-loaded sepiolite is added. After the addition is completed, the constant temperature stirring is continued for 12 hours, and anhydrous ethanol is added dropwise to the reactor at a speed of 1 mL / s. After the dropwise addition is completed, the stirring is continued for 2 hours, and then the temperature is cooled to room temperature, the material is discharged and filtered, and the filtered solid is washed with anhydrous ethanol for 3 times, and then dried at 85°C for 6 hours to obtain the modified sepiolite loaded with phytic acid; The particle size of the nano sepiolite is 100 nm; The density of the maleic anhydride grafted polyethylene is 0.96 g / cm 3 , the melt index is 6g / 10min at 190℃ / 2.16kg, and the melting temperature is 126℃; The mass ratio of the nano-sepiolite, acetone, tetradecyl dimethyl tertiary amine, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane, and phytic acid is 50:280:4:15:45; The mass ratio of the phytic acid-loaded sepiolite, maleic anhydride grafted polyethylene, toluene and anhydrous ethanol is 50:12:220:130.

[0015] Step 2: Preparation of ethylene-octene copolymer-coated expanded graphite Add ethylene octene copolymer and xylene into a reactor, control the stirring rate to 3900 rpm, raise the temperature and keep the temperature constant to 140°C, stir at the constant temperature under condensation reflux until the ethylene octene copolymer is completely dissolved, then add expanded graphite, after the addition is completed, continue to stir at the constant temperature for 14 hours, add anhydrous ethanol to the reactor at a rate of 2 mL / s, continue to stir for 3 hours after the addition is completed, cool to room temperature, filter the discharged material, wash the filtered solid with anhydrous ethanol 3 times, and place it at 55°C for 9 hours to obtain ethylene octene copolymer coated expanded graphite; The density of the ethylene octene copolymer is 0.87 g / cm 3, the melt index at 190℃ / 2.16kg is 2g / 10min, the Mooney viscosity at 121℃ / ML1+4 is 20MU, and the melting temperature is 50℃; The particle size of the expanded graphite is 500 mesh; The mass ratio of the ethylene octene copolymer, xylene, expanded graphite and anhydrous ethanol is 25:230:35:160.

[0016] Step 3: Preparation of modified hydroxide flame retardant The hydroxide was placed in an oven at 105° C. and dried for 12 hours, and then added to a dispersion reactor, and then toluene and sorbitan fatty acid ester were added, and the stirring rate was controlled to 8000 rpm, and the stirring rate was reduced to 3500 rpm, and then the temperature was raised and kept constant at 85° C., and 3-isocyanate propyltrimethoxysilane was added under a condensation reflux state, and the dispersion reaction was continued at a constant temperature for 5 hours, and then liquid polybutadiene rubber was added, and the dispersion reaction was continued for 8 hours, and then the temperature was cooled to room temperature, and the discharged material was filtered, and the filtered solid was washed with anhydrous ethanol for 3 times, and then dried in an oven at 80° C. for 7 hours to obtain a modified hydroxide flame retardant; The hydroxide is powdered aluminum hydroxide with a particle size of 1 μm; The liquid polybutadiene rubber has a number average molecular weight of 3500 g / mol and a viscosity of 6 Pa·s at 40° C.; The liquid polybutadiene rubber is a carboxyl-terminated liquid polybutadiene rubber; The mass ratio of the hydroxide, toluene, sorbitan fatty acid ester, 3-isocyanate propyltrimethoxysilane and liquid polybutadiene rubber is 90:260:3:25:25.

[0017] Step 4: Preparation of modified nano-hydrotalcite flame retardant After the nano-hydrotalcite is placed in a 95° C. oven and dried for 10 hours, the nano-hydrotalcite is added to a dispersion reactor, and then xylene and octylphenol polyoxyethylene ether are added. After the stirring rate is controlled at 9500 rpm and the dispersion is vigorously stirred for 9 hours, the stirring rate is reduced to 3500 rpm, and the temperature is then raised and kept constant at 130° C., and aromatic diacyl chloride is added under a condensation reflux state, and the dispersion reaction is continued at a constant temperature for 9 hours, and then a long-chain hydrocarbon primary amine is added, and the dispersion reaction is continued for 9 hours, and then the temperature is cooled to room temperature, the discharged material is filtered, and the filtered solid is washed with anhydrous ethanol for 3 times, and then dried in a 75° C. oven for 11 hours to obtain a modified hydroxide flame retardant; The particle size of the nano hydrotalcite is 60 nm; The aryl diacetyl chloride is 1,4-phenylene diacetyl chloride; The long-chain hydrocarbon primary amine is 12-tricosylamine; The mass ratio of the nano-hydrotalcite, xylene, octylphenol polyoxyethylene ether, aryl diacyl chloride and long-chain hydrocarbon primary amine is 50:240:2:11:18.

[0018] Step 5: Preparation of halogen-free flame-retardant polyethylene core material The specific formula of the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels is, in parts by weight: 200 parts of low-density polyethylene, 100 parts of high-density polyethylene, 50 parts of ethylene-ethyl acrylate copolymer, Modified sepiolite loaded with phytic acid 20 parts, 10 parts of ethylene octene copolymer coated expanded graphite, 30 parts of modified hydroxide flame retardant, 10 parts of modified nano hydrotalcite flame retardant, Lubricant polyethylene wax 7 parts; The low-density polyethylene has a melting temperature of 108°C and a density of 0.919 g / cm 3 , the melt flow rate is 14g / 10min at 190℃ / 2.16kg; The high-density polyethylene has a melting temperature of 120°C and a density of 0.948g / cm 3 , the melt flow rate is 11g / 10min at 190℃ / 2.16kg; The ethylene-ethyl acrylate copolymer has a melting temperature of 101°C and a density of 0.928 g / cm 3 , the melt flow rate is 9 g / 10 min at 190 ° C / 2.16 kg, and the content of ethyl acrylate is 18 wt%; According to the specific formula of the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels in parts by weight, corresponding parts by weight of low-density polyethylene, high-density polyethylene, ethylene-ethyl acrylate copolymer, modified sepiolite loaded with phytic acid, ethylene-octene copolymer coated expanded graphite, modified hydroxide flame retardant, modified nano-hydrotalcite flame retardant and lubricant polyethylene wax are put into a high-speed mixer and stirred and mixed. The mixing temperature is controlled at 80° C. and the stirring speed is 800 rpm. After stirring and mixing for 22 minutes, the mixed materials are sent to a twin-screw extruder. The heating zone of the twin-screw extruder is controlled at 190° C. and the die temperature is controlled at 205° C. The extrusion granulation is carried out, and the obtained resin particles are air-cooled to room temperature to obtain the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels.

[0019] Example 2: A halogen-free flame-retardant polyethylene core material for fireproof aluminum-plastic panels for decoration Step 1: Preparation of modified sepiolite loaded with phytic acid After the nano-sepiolite was placed in a 90°C oven and dried for 7 hours, it was added to a dispersion reactor, and then acetone and tetradecyl dimethyl tertiary amine were added. The stirring rate was controlled at 5500 rpm, and the dispersion was vigorously stirred for 6 hours. The stirring rate was reduced to 2500 rpm, and then the temperature was raised and kept constant at 40°C. N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added under condensation reflux. After the constant temperature dispersion reaction was performed for 4 hours, the temperature was lowered to room temperature, and then phytic acid was added. After the phytic acid was completely dissolved, the dispersion was stopped, and the material was allowed to stand for 24 hours. The solid was filtered, and the filtered solid was placed in a 40°C oven and dried for 5 hours to obtain a negative Phytic acid-loaded sepiolite, then maleic anhydride grafted polyethylene and toluene are added to a dry and clean stirred reactor, the stirring rate is controlled at 2000 rpm, the temperature is raised and kept constant at 110°C, and the maleic anhydride grafted polyethylene is stirred at a constant temperature under condensation reflux until the maleic anhydride grafted polyethylene is completely dissolved, and then the phytic acid-loaded sepiolite is added. After the addition is completed, the constant temperature stirring is continued for 7 hours, and anhydrous ethanol is added dropwise to the reactor at a rate of 0.5 mL / s. After the addition is completed, the stirring is continued for 1 hour, and then the temperature is cooled to room temperature, the material is filtered, and the filtered solid is washed twice with anhydrous ethanol, and then dried at 70°C for 5 hours to obtain the modified sepiolite loaded with phytic acid; The particle size of the nano sepiolite is 20 nm; The density of the maleic anhydride grafted polyethylene is 0.93 g / cm 3 , the melt index is 3g / 10min at 190℃ / 2.16kg, and the melting temperature is 120℃; The mass ratio of the nano-sepiolite, acetone, tetradecyl dimethyl tertiary amine, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane, and phytic acid is 35:150:1:6:25; The mass ratio of the phytic acid-loaded sepiolite, maleic anhydride grafted polyethylene, toluene and anhydrous ethanol is 30:8:190:80.

[0020] Step 2: Preparation of ethylene-octene copolymer-coated expanded graphite Add ethylene octene copolymer and xylene into a reactor, control the stirring rate to 3000 rpm, raise the temperature and keep the temperature constant to 120°C, stir at a constant temperature under condensation reflux until the ethylene octene copolymer is completely dissolved, then add expanded graphite, continue to stir at a constant temperature for 10 hours after the addition is complete, add anhydrous ethanol dropwise into the reactor at a rate of 1 mL / s, continue to stir for 2 hours after the addition is complete, cool to room temperature, filter the discharged material, wash the filtered solid with anhydrous ethanol twice, and dry it at 40°C for 6 hours to obtain ethylene octene copolymer-coated expanded graphite; The density of the ethylene octene copolymer is 0.85 g / cm 3, the melt index at 190℃ / 2.16kg is 1g / 10min, the Mooney viscosity at 121℃ / ML1+4 is 18MU, and the melting temperature is 48℃; The particle size of the expanded graphite is 300 mesh; The mass ratio of the ethylene octene copolymer, xylene, expanded graphite and anhydrous ethanol is 10:130:10:80.

[0021] Step 3: Preparation of modified hydroxide flame retardant The hydroxide was placed in a 90°C oven for drying for 6 hours, and then added to a dispersion reactor, and then toluene and sorbitan fatty acid ester were added, and the stirring rate was controlled to be 5000 rpm, and the stirring rate was reduced to 2000 rpm, and then the temperature was raised and kept constant at 70°C, and 3-isocyanate propyltrimethoxysilane was added under a condensation reflux state, and the dispersion reaction was continued at a constant temperature for 3 hours, and then liquid polybutadiene rubber was added, and the dispersion reaction was continued for 5 hours, and then the temperature was cooled to room temperature, and the material was filtered, and the filtered solid was washed with anhydrous ethanol twice, and dried in a 60°C oven for 4 hours to obtain a modified hydroxide flame retardant; The hydroxide is powdered magnesium hydroxide with a particle size of 0.5 μm; The liquid polybutadiene rubber has a number average molecular weight of 2000 g / mol and a viscosity of 3 Pa·s at 40° C.; The liquid polybutadiene rubber is a hydroxyl-terminated liquid polybutadiene rubber; The mass ratio of the hydroxide, toluene, sorbitan fatty acid ester, 3-isocyanate propyltrimethoxysilane and liquid polybutadiene rubber is 60:160:1:10:10.

[0022] Step 4: Preparation of modified nano-hydrotalcite flame retardant After the nano-hydrotalcite is placed in an oven at 80° C. and dried for 7 hours, the nano-hydrotalcite is added to a dispersion reactor, and then xylene and octylphenol polyoxyethylene ether are added. After the stirring rate is controlled at 8000 rpm and the dispersion is vigorously stirred for 6 hours, the stirring rate is reduced to 3000 rpm, and the temperature is then raised and kept constant at 100° C., and aromatic diacyl chloride is added under a condensation reflux state, and the dispersion reaction is continued at a constant temperature for 5 hours, and then a long-chain hydrocarbon primary amine is added, and the dispersion reaction is continued for 6 hours, and then the temperature is cooled to room temperature, and the discharged material is filtered, and the filtered solid is washed twice with anhydrous ethanol, and then dried in an oven at 60° C. for 8 hours to obtain a modified hydroxide flame retardant; The particle size of the nano hydrotalcite is 10 nm; The aryl diacyl chloride is 2,2-bipyridine-5,5-acyl chloride; The long-chain hydrocarbon primary amine is octadecyl primary amine; The mass ratio of the nano-hydrotalcite, xylene, octylphenol polyoxyethylene ether, aryl diacyl chloride and long-chain hydrocarbon primary amine is 20:140:1:7:9.

[0023] Step 5: Preparation of halogen-free flame-retardant polyethylene core material The specific formula of the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels is, in parts by weight: 160 parts of low-density polyethylene, 80 parts of high-density polyethylene, 15 parts of ethylene-ethyl acrylate copolymer, Modified sepiolite loaded with phytic acid 10 parts, 5 parts of ethylene octene copolymer coated expanded graphite, 15 parts of modified hydroxide flame retardant, 5 parts of modified nano hydrotalcite flame retardant, Lubricant polyethylene wax 4 parts; The low-density polyethylene has a melting temperature of 105°C and a density of 0.916 g / cm 3 , the melt flow rate is 10g / 10min at 190℃ / 2.16kg; The high-density polyethylene has a melting temperature of 115°C and a density of 0.944g / cm 3 , the melt flow rate is 8g / 10min at 190℃ / 2.16kg; The ethylene-ethyl acrylate copolymer has a melting temperature of 95°C and a density of 0.920 g / cm 3 , the melt flow rate is 5 g / 10 min at 190 ° C / 2.16 kg, and the content of ethyl acrylate is 15 wt%; According to the specific formula of the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels in parts by weight, corresponding parts by weight of low-density polyethylene, high-density polyethylene, ethylene-ethyl acrylate copolymer, modified sepiolite loaded with phytic acid, ethylene-octene copolymer coated expanded graphite, modified hydroxide flame retardant, modified nano-hydrotalcite flame retardant and lubricant polyethylene wax are put into a high-speed mixer and stirred and mixed. The mixing temperature is controlled at 60° C. and the stirring speed is 600 rpm. After stirring and mixing for 15 minutes, the mixed materials are sent to a twin-screw extruder. The heating zone of the twin-screw extruder is controlled at 170° C. and the die head temperature is controlled at 190° C. The extrusion is granulated, and the obtained resin particles are air-cooled to room temperature to obtain the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels.

[0024] Example 3: A halogen-free flame-retardant polyethylene core material for fireproof aluminum-plastic panels for decoration Step 1: Preparation of modified sepiolite loaded with phytic acid After the nano-sepiolite was placed in a 120°C oven and dried for 14 hours, it was added to a dispersion reactor, and then acetone and tetradecyl dimethyl tertiary amine were added. The stirring rate was controlled at 9000 rpm, and the dispersion was vigorously stirred for 14 hours. The stirring rate was reduced to 4800 rpm, and then the temperature was raised and kept constant at 60°C. N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added under the condensation reflux state. After the constant temperature dispersion reaction for 9 hours, the temperature was cooled to room temperature, and then phytic acid was added. After the phytic acid was completely dissolved, the dispersion was stopped, and the material was filtered after standing for 45 hours. The filtered solid was placed in a 70°C oven and dried for 10 hours to obtain a load. Phytic acid-loaded sepiolite, then maleic anhydride grafted polyethylene and toluene are added to a dry and clean stirred reactor, the stirring rate is controlled at 4000 rpm, the temperature is raised and kept constant at 130°C, and the maleic anhydride grafted polyethylene is stirred at a constant temperature under condensation reflux until the maleic anhydride grafted polyethylene is completely dissolved, and then the phytic acid-loaded sepiolite is added. After the addition is completed, the constant temperature stirring is continued for 15 hours, and anhydrous ethanol is added dropwise to the reactor at a rate of 1.3 mL / s. After the addition is completed, the stirring is continued for 2.5 hours, and then the temperature is cooled to room temperature. The material is filtered, and the filtered solid is washed with anhydrous ethanol 4 times, and then dried at 90°C for 8.5 hours to obtain the modified sepiolite loaded with phytic acid; The particle size of the nano sepiolite is 200 nm; The density of the maleic anhydride grafted polyethylene is 0.97 g / cm 3 , the melt index is 8g / 10min at 190℃ / 2.16kg, and the melting temperature is 130℃; The mass ratio of the nano-sepiolite, acetone, tetradecyl dimethyl tertiary amine, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane, and phytic acid is 60: 330:5:25:55; The mass ratio of the phytic acid-loaded sepiolite, maleic anhydride grafted polyethylene, toluene and anhydrous ethanol is 80:20:250:160.

[0025] Step 2: Preparation of ethylene-octene copolymer-coated expanded graphite Add ethylene octene copolymer and xylene into a reactor, control the stirring rate to 6000 rpm, raise the temperature and keep the temperature constant to 150°C, stir at the constant temperature under condensation reflux until the ethylene octene copolymer is completely dissolved, then add expanded graphite, continue to stir at the constant temperature for 17 hours after the addition is complete, add anhydrous ethanol dropwise into the reactor at a rate of 2.5 mL / s, continue to stir for 4.5 hours after the addition is complete, cool to room temperature, filter the discharged material, wash the filtered solid with anhydrous ethanol 4 times, and dry it at 60°C for 10 hours to obtain ethylene octene copolymer-coated expanded graphite; The density of the ethylene octene copolymer is 0.88 g / cm 3, the melt index at 190℃ / 2.16kg is 3.5g / 10min, the Mooney viscosity at 121℃ / ML1+4 is 23MU, and the melting temperature is 53℃; The particle size of the expanded graphite is 600 mesh; The mass ratio of the ethylene-octene copolymer, xylene, expanded graphite and anhydrous ethanol is 30:290:50:190.

[0026] Step 3: Preparation of modified hydroxide flame retardant The hydroxide was placed in an oven at 110° C. and dried for 16 hours, and then added to a dispersion reactor, and then toluene and sorbitan fatty acid ester were added, and the stirring rate was controlled at 9500 rpm, and the stirring rate was reduced to 4500 rpm, and then the temperature was raised and kept constant at 90° C., and 3-isocyanate propyltrimethoxysilane was added under a condensation reflux state, and the dispersion reaction was continued at a constant temperature for 6 hours, and then liquid polybutadiene rubber was added, and the dispersion reaction was continued for 9 hours, and then the temperature was cooled to room temperature, and the discharged material was filtered, and the filtered solid was washed with anhydrous ethanol for 4 times, and then dried in an oven at 90° C. for 9 hours to obtain a modified hydroxide flame retardant; The hydroxide is powdered aluminum hydroxide with a particle size of 3 μm; The liquid polybutadiene rubber has a number average molecular weight of 5500 g / mol and a viscosity of 8 Pa·s at 40° C.; The liquid polybutadiene rubber is a carboxyl-terminated liquid polybutadiene rubber; The mass ratio of the hydroxide, toluene, sorbitan fatty acid ester, 3-isocyanate propyltrimethoxysilane and liquid polybutadiene rubber is 110:360:4:35:40.

[0027] Step 4: Preparation of modified nano-hydrotalcite flame retardant After the nano-hydrotalcite is placed in an oven at 100° C. and dried for 15 hours, the nano-hydrotalcite is added to a dispersion reactor, and then xylene and octylphenol polyoxyethylene ether are added, and the stirring rate is controlled at 10,000 rpm, and the dispersion is vigorously stirred for 10 hours, and then the stirring rate is reduced to 4,500 rpm, and then the temperature is raised and kept constant at 140° C., and aromatic diacyl chloride is added under a condensation reflux state, and the dispersion reaction is continued at a constant temperature for 11 hours, and then a long-chain hydrocarbon primary amine is added, and the dispersion reaction is continued for 10 hours, and then the temperature is cooled to room temperature, and the material is filtered, and the filtered solid is washed with anhydrous ethanol for 4 times, and then dried in an oven at 80° C. for 13 hours to obtain a modified hydroxide flame retardant; The particle size of the nano hydrotalcite is 100 nm; The aryl diacyl chloride is 4,4'-diacyl chloride diphenyl ether; The long-chain hydrocarbon primary amine is coconut oil alkyl primary amine; The mass ratio of the nano-hydrotalcite, xylene, octylphenol polyoxyethylene ether, aryl diacyl chloride and long-chain hydrocarbon primary amine is 70:300:2.5:19:25.

[0028] Step 5: Preparation of halogen-free flame-retardant polyethylene core material The specific formula of the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels is, in parts by weight: 250 parts of low-density polyethylene, 140 parts of high-density polyethylene, 70 parts of ethylene-ethyl acrylate copolymer, Modified sepiolite loaded with phytic acid 35 parts, 25 parts of ethylene octene copolymer coated expanded graphite, 55 parts of modified hydroxide flame retardant, 20 parts of modified nano hydrotalcite flame retardant, Lubricant polyethylene wax 12 parts; The low-density polyethylene has a melting temperature of 115°C and a density of 0.925 g / cm 3 , the melt flow rate is 25g / 10min at 190℃ / 2.16kg; The high-density polyethylene has a melting temperature of 130°C and a density of 0.954 g / cm 3 , the melt flow rate is 13g / 10min at 190℃ / 2.16kg; The ethylene-ethyl acrylate copolymer has a melting temperature of 105°C and a density of 0.935 g / cm 3 , the melt flow rate is 11 g / 10 min at 190 ° C / 2.16 kg, and the content of ethyl acrylate is 20 wt%; According to the specific formula of the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels in parts by weight, corresponding parts by weight of low-density polyethylene, high-density polyethylene, ethylene-ethyl acrylate copolymer, modified sepiolite loaded with phytic acid, ethylene-octene copolymer coated expanded graphite, modified hydroxide flame retardant, modified nano-hydrotalcite flame retardant and lubricant polyethylene wax are put into a high-speed mixer for stirring and mixing. The mixing temperature is controlled at 95° C. and the stirring speed is 950 rpm. After stirring and mixing for 35 minutes, the mixed materials are sent to a twin-screw extruder. The heating zone of the twin-screw extruder is controlled at 220° C. and the die head temperature is controlled at 210° C. The extrusion granulation is carried out. The obtained resin particles are air-cooled to room temperature to obtain the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels.

[0029] Comparative Example 1: Based on Example 1, step 1, preparation of modified sepiolite loaded with phytic acid, is not performed. In step 5, preparation of halogen-free flame-retardant polyethylene core layer material, modified sepiolite loaded with phytic acid is not added, and 20 parts of modified sepiolite loaded with phytic acid are replaced by 20 parts of low-density polyethylene in equal amounts. The specific operations are as follows: Step 1, preparation of modified sepiolite loaded with phytic acid, is not performed; The operations of steps 2, 3, and 4 are the same as those of Example 1; Step 5: Preparation of halogen-free flame-retardant polyethylene core material The 20 parts of modified sepiolite loaded with phytic acid were replaced by 20 parts of low-density polyethylene, and the other operations were the same as in Example 1.

[0030] Comparative Example 2: Based on Example 1, step 2, preparation of ethylene octene copolymer-coated expanded graphite, is not performed. In step 5, preparation of halogen-free flame-retardant polyethylene core layer material, ethylene octene copolymer-coated expanded graphite is not added, and 10 parts of ethylene octene copolymer-coated expanded graphite are replaced by 10 parts of low-density polyethylene in equal amounts. The specific operations are as follows: The operation of step 1 is the same as that of embodiment 1; Step 2, preparation of ethylene-octene copolymer-coated expanded graphite is not performed; The operations of steps 3 and 4 are the same as those of Example 1; Step 5: Preparation of halogen-free flame-retardant polyethylene core material The 10 parts of ethylene octene copolymer-coated expanded graphite were replaced by 10 parts of low-density polyethylene in equal amounts, and the other operations were the same as in Example 1.

[0031] Comparative Example 3: Based on Example 1, step 3, preparation of modified hydroxide flame retardant, is not performed. In step 5, preparation of halogen-free flame retardant polyethylene core material, modified hydroxide flame retardant is not added, 30 parts of modified hydroxide flame retardant are replaced by 30 parts of low-density polyethylene in equal amounts, and the specific operation is as follows: The operations of steps 1 and 2 are the same as those of Example 1; Step 3, preparation of modified hydroxide flame retardant is not performed; Step 5: Preparation of halogen-free flame-retardant polyethylene core material 30 parts of modified hydroxide flame retardant were replaced by 30 parts of low-density polyethylene, and other operations were the same as in Example 1.

[0032] Comparative Example 4: Based on Example 1, step 4, preparation of modified nano-hydrotalcite flame retardant, is not performed. In step 5, preparation of halogen-free flame-retardant polyethylene core material, modified nano-hydrotalcite flame retardant is not added, and 10 parts of modified nano-hydrotalcite flame retardant are replaced by 10 parts of low-density polyethylene in equal amounts. The specific operation is as follows: The operations of steps 1, 2, and 3 are the same as those of Example 1; Step 4, preparation of modified nano-hydrotalcite flame retardant is not performed; Step 5: Preparation of halogen-free flame-retardant polyethylene core material 10 parts of modified nano-hydrotalcite flame retardant were replaced by 10 parts of low-density polyethylene in equal amount, and other operations were the same as in Example 1.

[0033] Performance Test: The halogen-free flame-retardant polyethylene core layer material for decorative fireproof aluminum-plastic panels obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4 was tested for the following indicators: 1. Tensile strength: Tested in accordance with GB / T1040.2-2006; 2. Elongation at break: Tested in accordance with GB / T1040.2-2006; 3. Impact strength: Tested in accordance with GB / T1843-2008; 4. Bending strength: Tested in accordance with GB / T8812.2-2007; 5. Oxygen index: Tested in accordance with GB / T2406.1-2008; The test results of the above indicators are shown in Table 1: Table 1 From the data in Table 1, it can be seen that the tensile strength of Examples 1-3 is all above 24 MPa, the elongation at break is greater than 41%, and the impact strength is also all above 47 kJ / m 2The above, the bending strength is greater than 25Mpa, the oxygen index is above 40, which shows that the halogen-free flame retardant polyethylene core layer material for decoration and fireproof aluminum-plastic panel prepared by the present invention has relatively excellent mechanical properties and very good flame retardant properties; in Comparative Example 1 without adding modified sepiolite-loaded phytic acid, the tensile strength, elongation at break, and impact strength are all less than those in Example 1, the flexural strength is slightly greater than that in Example 1, but the oxygen index drops sharply to 26.7, which shows that the modified sepiolite-loaded phytic acid has a relatively obvious strengthening and toughening effect on the halogen-free flame retardant polyethylene core layer material, and only has a relatively slight negative impact on the flexural strength, but the modified sepiolite-loaded phytic acid plays a very important role in improving the flame retardant properties of the halogen-free flame retardant polyethylene core layer material; Comparative Example 2 does not add ethylene-octene copolymer-coated expanded graphite, the tensile strength, elongation at break, impact strength, and flexural strength of Comparative Example 2 are slightly greater than those of Example 1, but the oxygen index of Comparative Example 2 drops sharply to 23.3, which shows that the ethylene-octene copolymer-coated expanded graphite The coated expanded graphite has a slight effect on the mechanical properties of the halogen-free flame retardant polyethylene core layer material, but it has a more critical role in improving the flame retardant properties of the halogen-free flame retardant polyethylene core layer material; in Example 3, no modified hydroxide flame retardant is added, and the elongation at break, impact strength and flexural strength of Example 3 are slightly better than those of Example 1, and the tensile strength is slightly worse than that of Example 1, but the oxygen index of Example 3 is much lower than that of Example 1, which shows that the modified hydroxide flame retardant has a relatively slight negative impact on the mechanical properties of the halogen-free flame retardant polyethylene core layer material, but can also greatly improve the flame retardant properties of the halogen-free flame retardant polyethylene core layer material; in Example 4, no modified nano-hydrotalcite flame retardant is added, and the tensile strength, elongation at break, impact strength and flexural strength of Example 4 are significantly lower than those of Example 1, and the oxygen index is also significantly lower than that of Example 1, which shows that the modified nano-hydrotalcite flame retardant not only plays a role in improving the mechanical properties of the halogen-free flame retardant polyethylene core layer material, but also can improve its flame retardant properties.

[0034] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A halogen-free flame-retardant polyethylene core material for fireproof aluminum-plastic panels for decoration, characterized by: The specific formula of the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels is, in parts by weight: 160~250 parts of low-density polyethylene, 80~140 parts of high-density polyethylene, 15-70 parts of ethylene-ethyl acrylate copolymer, Modified sepiolite loaded with phytic acid 10-35 parts, 5-25 parts of ethylene octene copolymer coated expanded graphite, 15-55 parts of modified hydroxide flame retardant, 5-20 parts of modified nano hydrotalcite flame retardant, Lubricant polyethylene wax 4-12 parts; The low-density polyethylene has a melting temperature of 105-115°C and a density of 0.916-0.925 g / cm 3 , melt flow rate is 10~25g / 10min at 190℃ / 2.16kg; The high-density polyethylene has a melting temperature of 115-130°C and a density of 0.944-0.954 g / cm 3 , the melt flow rate is 8~13g / 10min at 190℃ / 2.16kg; The ethylene-ethyl acrylate copolymer has a melting temperature of 95-105°C and a density of 0.920-0.935 g / cm 3 , the melt flow rate is 5~11g / 10min at 190℃ / 2.16kg, and the content of ethyl acrylate is 15~20wt%.

2. The halogen-free flame-retardant polyethylene core material for fireproof aluminum-plastic panels for decoration and decoration according to claim 1, characterized in that: The modified sepiolite loaded with phytic acid has a preparation method comprising: placing the nano sepiolite in an oven at 90-120°C for drying for 7-14 hours, adding the nano sepiolite to a dispersion reaction kettle, then adding acetone and tetradecyl dimethyl tertiary amine, controlling the stirring rate at 5500-9000 rpm, vigorously stirring and dispersing for 6-14 hours, reducing the stirring rate to 2500-4800 rpm, then heating and maintaining the temperature at 40-60°C, adding N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane under a condensation reflux state, performing a constant temperature dispersion reaction for 4-9 hours, cooling the temperature to room temperature, then adding phytic acid, stopping dispersion after the phytic acid is completely dissolved, standing for 24-45 hours, filtering the discharged material, and drying the filtered solid in an oven at 40-70°C. After drying for 5 to 10 hours, phytic acid-loaded sepiolite is obtained, and then maleic anhydride grafted polyethylene and toluene are added to a dry and clean stirred reactor, and the stirring rate is controlled at 2000 to 4000 rpm, and the temperature is raised and kept constant at 110 to 130° C., and the maleic anhydride grafted polyethylene is stirred at a constant temperature under condensation reflux until the maleic anhydride grafted polyethylene is completely dissolved, and then the phytic acid-loaded sepiolite is added. After the addition is completed, the constant temperature stirring is continued for 7 to 15 hours, and anhydrous ethanol is added dropwise to the reactor at a speed of 0.5 to 1.3 mL / s. After the dropwise addition is completed, the stirring is continued for 1 to 2.5 hours, and then the mixture is cooled to room temperature, and the material is filtered. The filtered solid is washed with anhydrous ethanol for 2 to 4 times, and then dried at 70 to 90° C. for 5 to 8.5 hours to obtain the modified sepiolite loaded with phytic acid; The particle size of the nano sepiolite is 20-200 nm; The density of the maleic anhydride grafted polyethylene is 0.93-0.97 g / cm 3 The melt index is 3~8g / 10min at 190℃ / 2.16kg, and the melting temperature is 120~130℃.

3. The halogen-free flame-retardant polyethylene core material for fireproof aluminum-plastic panels for decoration and decoration according to claim 1, characterized in that: The ethylene-octene copolymer-coated expanded graphite has a preparation method comprising: adding the ethylene-octene copolymer and xylene into a reaction kettle, controlling the stirring rate to 3000-6000 rpm, heating and maintaining the temperature to 120-150° C., stirring at a constant temperature under condensation reflux until the ethylene-octene copolymer is completely dissolved, then adding expanded graphite, and after the addition is completed, continuing to stir at a constant temperature for 10-17 hours, and then dripping anhydrous ethanol into the kettle at a speed of 1-2.5 mL / s, and after the dripping is completed, continuing to stir for 2-4.5 hours, cooling to room temperature, discharging and filtering, washing the filtered solid with anhydrous ethanol for 2-4 times, and drying at 40-60° C. for 6-10 hours to obtain the ethylene-octene copolymer-coated expanded graphite; The density of the ethylene octene copolymer is 0.85-0.88 g / cm 3 , the melt index at 190℃ / 2.16kg is 1~3.5g / 10min, the Mooney viscosity at 121℃ / ML1+4 is 18~23MU, and the melting temperature is 48~53℃; The particle size of the expanded graphite is 300-600 meshes.

4. The halogen-free flame-retardant polyethylene core material for fireproof aluminum-plastic panels for decoration and decoration according to claim 1, characterized in that: The modified hydroxide flame retardant has a preparation method comprising: placing the hydroxide in an oven at 90-110°C and drying for 6-16 hours, adding the hydroxide to a dispersion reaction kettle, then adding toluene and sorbitan fatty acid ester, controlling the stirring rate to 5000-9500 rpm, vigorously stirring and dispersing for 5-11 hours, reducing the stirring rate to 2000-4500 rpm, then heating and maintaining the temperature at 70-90°C, adding 3-isocyanate propyltrimethoxysilane under a condensation reflux state, performing a constant temperature dispersion reaction for 3-6 hours, then adding liquid polybutadiene rubber, continuing the dispersion reaction for 5-9 hours, cooling to room temperature, discharging and filtering, washing the filtered solid with anhydrous ethanol for 2-4 times, and drying it in an oven at 60-90°C for 4-9 hours to obtain the modified hydroxide flame retardant; The hydroxide is one of powdered aluminum hydroxide and powdered magnesium hydroxide, and the particle size is 0.5-3 μm; The liquid polybutadiene rubber has a number average molecular weight of 2000-5500 g / mol and a viscosity of 3-8 Pa·s at 40° C.; The liquid polybutadiene rubber is one of carboxyl-terminated liquid polybutadiene rubber and hydroxyl-terminated liquid polybutadiene rubber.

5. The halogen-free flame-retardant polyethylene core material for fireproof aluminum-plastic panels for decoration and decoration according to claim 1, characterized in that: The modified nano hydrotalcite flame retardant is prepared by: placing the nano hydrotalcite in an oven at 80-100°C and drying for 7-15 hours, adding the nano hydrotalcite to a dispersion reaction kettle, then adding xylene and octylphenol polyoxyethylene ether, controlling the stirring rate to 8000-10000 rpm, vigorously stirring and dispersing for 6-10 hours, reducing the stirring rate to 3000-4500 rpm, then heating and maintaining the temperature at 100-140°C, adding aryl dichloride under a condensation reflux state, performing a constant temperature dispersion reaction for 5-11 hours, then adding a long-chain hydrocarbon primary amine, continuing the dispersion reaction for 6-10 hours, cooling to room temperature, discharging and filtering, washing the filtered solid with anhydrous ethanol for 2-4 times, and drying it in an oven at 60-80°C for 8-13 hours to obtain a modified hydroxide flame retardant; The particle size of the nano hydrotalcite is 10-100 nm; The aromatic diacyl chloride is one of 1,4-phenylenediacetyl chloride, 2,2-bipyridine-5,5-acyl chloride, and 4,4'-diacyl chloride diphenyl ether; The long-chain hydrocarbon primary amine is one of 12-tricosylamine, octadecyl primary amine and coconut oil alkyl primary amine.

6. The halogen-free flame-retardant polyethylene core material for fireproof aluminum-plastic panels for decoration and decoration according to claim 2, characterized in that: The mass ratio of the nano-sepiolite, acetone, tetradecyl dimethyl tertiary amine, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane and phytic acid is 35-60:150-330:1-5:6-25:25-55; The mass ratio of the phytic acid-loaded sepiolite, maleic anhydride grafted polyethylene, toluene and anhydrous ethanol is 30-80:8-20:190-250:80-160.

7. The halogen-free flame-retardant polyethylene core material for fireproof aluminum-plastic panels for decoration and decoration according to claim 3 is characterized by: The mass ratio of the ethylene-octene copolymer, xylene, expanded graphite and anhydrous ethanol is 10-30:130-290:10-50:80-190.

8. The halogen-free flame-retardant polyethylene core material for fireproof aluminum-plastic panels for decoration and decoration according to claim 4, characterized in that: The mass ratio of the hydroxide, toluene, sorbitan fatty acid ester, 3-isocyanate propyltrimethoxysilane and liquid polybutadiene rubber is 60-110:160-360:1-4:10-35:10-40.

9. The halogen-free flame-retardant polyethylene core material for fireproof aluminum-plastic panels for decoration and decoration according to claim 5, characterized in that: The mass ratio of the nano-hydrotalcite, xylene, octylphenol polyoxyethylene ether, aryl diacyl chloride and long-chain hydrocarbon primary amine is 20-70:140-300:1-2.5:7-19:9-25.

10. The halogen-free flame-retardant polyethylene core material for fireproof aluminum-plastic panels for decoration and decoration according to claim 1, characterized in that: The halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels has a preparation method comprising: according to the specific formula of the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels in parts by weight, corresponding parts by weight of low-density polyethylene, high-density polyethylene, ethylene-ethyl acrylate copolymer, modified sepiolite loaded with phytic acid, ethylene-octene copolymer coated expanded graphite, modified hydroxide flame retardant, modified nano hydrotalcite flame retardant, and lubricant polyethylene wax are put into a high-speed mixer for stirring and mixing; the mixing temperature is controlled at 60-95° C., the stirring speed is controlled at 600-950 rpm, and after stirring and mixing for 15-35 minutes, the mixed materials are sent into a twin-screw extruder, the heating zone of the twin-screw extruder is controlled at 170-220° C., the die head temperature is controlled at 190-210° C., extrusion granulation is performed, and the obtained resin particles are air-cooled to room temperature to obtain the halogen-free flame-retardant polyethylene core material for decorative fireproof aluminum-plastic panels.

Citation Information

Patent Citations

  • Aluminum plastic plate flame-retardant core layer and aluminum-plastic plate

    CN109111617A

  • Fireproof aluminum-plastic panel core material and preparation process thereof

    CN116478463A

  • Method for preparing halogen-free smoke-suppressant and flame-retardant plastic optical fiber sheath

    CN101950044A

  • Intumescent flame retardant functionalized hydrotalcite flame retardant and preparation method thereof

    CN105153467A

  • Halogen-free flame-retardant fireproof cable and preparation method thereof

    CN112961424A